Penguatan Daya Saing Bali Fine Craft Melalui Inovasi Kemasan Ramah Lingkungan Berbasis Ecoprint. - I Made Adi Suwandana (Jurnal Pengabdian Kepada Masyarakat, 2025)
Packaging adds value for SMEs, especially Bali Fine Craft with its sustainable ecoprint products. This program aims to design eco-friendly packaging that supports brand identity and attracts consumers. Methods include situational analysis, initial design, prototype development, strength and visual tests, and limited implementation. Results show recycled kraft and reusable linen pouches support the slow fashion concept and receive positive feedback. Digital marketing and educational campaigns help spread sustainability values to consumers. This innovation is expected to boost competitiveness and customer loyalty.